Gonadectomy affects brain derived neurotrophic factor in rats after chronic constriction nerve injury - ZHAO Xin; WANG Xin; ZHENG Shu-yun; XU Jian-guo (Acta Pharmacologica Sinica, 2016)
AIM: To assess the effect of gonadectomy on brain derived neurotrophic factor (BDNF) expression in neuropathic pain. METHODS: Using chronic constriction injury (CCI) model, we detected BDNF mRNA in dorsal root ganglion and protein content in spinal cord by reverse transcription polymerase chain reaction and enzyme-linked immunosorbent assay respectively. The time point we chose was post CCI operation d 0, 3, 7, 14, and 21. RESULTS: After CCI surgery, BDNF mRNA in ipsilateral DRGs was upregulated and reached its maximum on post operation d 7. BDNF protein level in ipsilateral spinal cord was also increased and reached its maximum on post operation d 14. The magnitude of this increase in gonadectomy (GDX) rats was significantly smaller than the GDX-sham rats at each time point. CONCLUSION: Gonadectomy reduced the BDNF increment after CCI surgery. Estrogen may affect nociceptive processing by its effect on BDNF.